Placement of Resonance Stent for Malignant or Benign Ureteral Obstruction - Cedars, Benjamin; Abedi, Garen; Sur, Roger L (Journal of endourology, 2021)
The aim of this article is to illustrate a step-by-step guide to placement of Resonance® metallic ureteral stent (Cook Medical, Bloomington, IN) for management of malignant or benign ureteral obstruction. In this article, the steps of operating room setup, patient positioning, gaining access to the upper urinary tract, and endoscopic and fluoroscopic placement of a Resonance ureteral stent are described.The aim of this article is to illustrate a step-by-step guide to placement of Resonance® metallic ureteral stent (Cook Medical, Bloomington, IN) for management of malignant or benign ureteral obstruction. In this article, the steps of operating room setup, patient positioning, gaining access to the upper urinary tract, and endoscopic and fluoroscopic placement of a Resonance ureteral stent are described.